1975
DOI: 10.1152/ajplegacy.1975.228.1.318
|View full text |Cite
|
Sign up to set email alerts
|

Transmural coronary venous O2 saturations in normal and isolated hearts

Abstract: Blood O2 saturations were measured by microscopic oximetry in the small coronary veins of wither open-chest or isolated and blood-perfused dog hearts. Subendocardial saturations (average 34%) were significantly lower than subepicardial (average 52%) in isolated hearts contracting isovolumically at systolic and coronary perfusion pressures of 100 mmHg. Saturations of botb regions fell and were not significantly different from each other (both averaged 16%) with partial coronary occlusion. When MVo2 was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1977
1977
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…As seen, the endocardial layers at normal preloads consume about 8% more oxygen than the epicardial layers, which is within the range obtained in experimental measurements (Gamble et al, 1974;Monroe et al, 1975;Weiss et al, 1978). However, the relative difference between the endocardial and epicardial layers seems to be highly preload dependent, actually inversing at very low preloads and increasing to 25% at high preloads.…”
Section: Layers At Normal and Increased Preloads Edv = End-diastolicsupporting
confidence: 83%
See 2 more Smart Citations
“…As seen, the endocardial layers at normal preloads consume about 8% more oxygen than the epicardial layers, which is within the range obtained in experimental measurements (Gamble et al, 1974;Monroe et al, 1975;Weiss et al, 1978). However, the relative difference between the endocardial and epicardial layers seems to be highly preload dependent, actually inversing at very low preloads and increasing to 25% at high preloads.…”
Section: Layers At Normal and Increased Preloads Edv = End-diastolicsupporting
confidence: 83%
“…However, data for the latter comparison is unattainable, and most of the techniques for measuring regional oxygen consumption encompass at least one-fourth of the wall thickness. The experimentally observed 20% higher oxygen consumption of the endocardial layers relative to the epicardial layers (Monroe et al, 1975;Weiss et al, 1978) is indeed consistent with our results.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…As the distribution of coronary flow between the epicardium and endocardium is one important factor for myocardial oxygen supply [24] an improved endocardial oxygen extraction can be expected in hearts perfused with pulsatile flow. The vulnerability of the endocardium to ischemia has been well documented [21,22] and higher oxygen extraction in this layer has been reported [17]. It seems that shorter periods of ventricular fibrillation in the presence of a coronary stenosis are well tolerated as no differences appeared between both types of perfusion during the first 20 min.…”
Section: Discussionmentioning
confidence: 89%
“…In the 1970s, experiments with animals showed that coronary flow is characterized by heterogeneity, reflected in a considerable difference in the myocardial capillary transit time [34] and in blood O 2 saturation [35]. This is easily explained by the fact that the mechanical load on the myocardial wall and, therefore, its metabolic activity are heterogeneous [2,3].…”
Section: Discussionmentioning
confidence: 99%